2018
DOI: 10.1016/j.najef.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the real impact of banking crises: A review and new evidence

Abstract: We examine which variables are robust in explaining cross-country differences in the real impact of systemic banking crises. Based on a meta-analysis, we identify 21 variables frequently used as determinants of the severity of crises. Employing nine proxies for crisis severity, we find that large current account imbalances are the most robust determinant of the real impact of banking crises. Countries with a high GDP per capita have more prolonged downfalls after the occurrence of a banking crisis. Exchange ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Based on Cecchetti et al (2009) and Wilms et al (2018), we consider in the vector X three sets of potential DBC determinants. Pre ‐ crisis proxies for macroeconomic, financial (including credit growth and credit boom variables) and institutional conditions preceding banking crises, and we distinguish between pre‐crisis internal and external conditions .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Cecchetti et al (2009) and Wilms et al (2018), we consider in the vector X three sets of potential DBC determinants. Pre ‐ crisis proxies for macroeconomic, financial (including credit growth and credit boom variables) and institutional conditions preceding banking crises, and we distinguish between pre‐crisis internal and external conditions .…”
Section: Methodsmentioning
confidence: 99%
“…The first, and most popular, comes from studies on the determinants of the output cost of banking crises and is based on a pre‐crisis referential. The second is based on the dynamics of one or several variables after the outbreak of banking crises (see, e.g., Angkinand, 2008, Cecchetti et al, 2009, or Wilms et al, 2018, for surveys on the measurement of the cost of banking crises).…”
Section: Datamentioning
confidence: 99%
“…Regulatory and supervision practices are not helpful in bankruptcy prevention (Pereira Pedro et al, 2018; Stef & Dimelis, 2020). Wilms et al (2018) and Igharo et al (2020) asserted that liquidity support, monetary policy, and financial freedom significantly affect the subsequent mitigation process of banking crises. Manz (2019) reported that loan and asset-specific events still lack a deeper understanding and deserve rigorous research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This historical and current excursus allows to study the speed of crisis propagation and the response to further prevent it: a better monitoring system that certainly cannot leave the cyclical and macroeconomic variables out of the ratings, given that the failure of a bank has systemic effects. Wilms et al (2018) identify 21 variables frequently used as determinants of the severity of banking crises but not yet included in the official ratings. The need to introduce a rating model closer to the new needs of the banking and financial market is therefore evident: our new "Bank-Tailored Integrated Rating" (BTIR) provides an important response in this direction.…”
Section: Stylized Facts: What the Evidence Showsmentioning
confidence: 99%